On the Promotion of TKX‐50 Thermal Activity with Aluminum. Issue 6 (25th April 2022) - Wang, Di; Guo, Xueyong; Wang, Zhenghong; Wang, Shuji; Wu, Chengcheng; Zhao, Wanjun; Fang, Hua
Abstract: It is significant to investigate the effect of aluminum (Al) on the thermal activity of Dihydroxylammonium 5, 5′‐bistetrazole‐1, 1′‐diolate (TKX‐50) for the application of TKX‐50‐based composite solid propellant. In this work, TKX‐50/Al composites with different particle sizes and contents of Al were blended, and the thermal decomposition and combustion properties were investigated by differential scanning calorimetry (DSC), thermal decomposition kinetic methods, laser ignition experiments, and constant‐volume combustion cell test. The results showed that the exothermic peak temperatures for thermal decomposition of TKX‐50 were gradually advanced with the decrease of Al particle size. With the increase of Al nanoparticles (nAl) content, the peak temperatures of TKX‐50 first decreased and then increased. As the content of nAl was 50 %, the activation energy of TKX‐50 changed from 226.51 kJ ⋅ mol −1 to 215.23 kJ ⋅ mol −1, and the critical temperature of thermal explosion decreased by 13.54 °C after the addition of nAl. In addition, a small amount of nAl could promote the combustion of TKX‐50 that is reflected on the accelerated burning rate, increased maximum combustion pressure and pressurization rate. Overall, nAl with high specific surface area and high reactivity is a great thermal activity enhancement additive for TKX‐50.